(Neo-)Adjuvant and first-line therapy: Prognostic and predictive factors (Neo-)Adjuvanten und First-Line-Therapie: Prognostische und prädiktive Faktoren - Lux, Michael P.; Oenuegoeren, Onur; Wunderle, Marius; Hein, Alexander; Rauh, Claudia; Schrauder, Michael G.; Fasching, Peter; Beckmann, Matthias (Gynäkologe, 2015)
The number of cancer cases is increasing steadily. In Germany, 97,480 women are diagnosed with a gynecological malignancy each year, which represents 43 % of all cancer cases in women. Furthermore, gynecological malignancies are responsible for 28 % of cancer deaths. These numbers highlight the need for optimal, individualized treatment decisions in order to achieve maximum effectiveness, prevent recurrence and metastatic progression, and avoid overtreatment. Reliable and validated prognostic and predictive factors are required for the therapy decision of (neo-)adjuvant or first-line treatment of patients with gynecological cancers or breast cancer. In the era of individualized and targeted therapy there are fewer predictive factors available than originally thought. Nevertheless, future perspectives for various tumor entities present promising approaches which can support therapeutic decisions for adjuvant systemic therapy, e.g. gene expression analyses, studies of gene copy variations or the detection of single mutations which play an important role in signaling pathways of tumor cells.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Antineoplastic agents; Biomarkers; Breast neoplasms; Decision making; Gene expression